Development of pattern recognition technique of partial discharge signal in high voltage underground cable - 391775 Chen, Yau Thong (Skudai : Universiti Teknologi Malaysia, 2002)
Project Paper (Bachelor of Electrical Engineering) - Universiti Teknologi Malaysia, 2002